TRANSFORMATION OF THE SYSTEM FOR DEVELOPING UKRAINE'S EXPORT POTENTIAL BASED ON THE TRADE EXPERIENCE OF G7 COUNTRIES - MOROZOVA, Olha (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The relevance of this research stems from the profound transformation of Ukraine’s foreign economic activity under conditions of full-scale war, disruption of trade relations, decline in industrial production, and logistical constraints. At the same time, exports remain a key factor in sustaining the balance of payments, currency stability, and economic recovery. Enhancing export potential is therefore viewed not only as an economic necessity but also as a strategic priority requiring coordinated interaction between state institutions, businesses, and international partners. The study addresses the problem of Ukraine’s fragmented and insufficiently coordinated export promotion system, which particularly hinders small and medium-sized enterprises due to limited access to financial, logistical, and analytical resources. Global transformations caused by military aggression and instability necessitate a systemic rethinking of export policy. The aim of the research is to substantiate theoretical foundations and propose a hierarchical model for strengthening Ukraine’s export potential, drawing on the trade experience of the G7 countries. A review of recent academic and institutional publications demonstrates wide coverage of Ukraine’s export challenges but insufficient attention to the development of a comprehensive multi-level model. Existing studies analyze structural shifts in trade, logistical disruptions, and institutional barriers, while reports by USAID, EBRD, UkraineInvest, and the Export Promotion Office emphasize the lack of effective coordination and SME support mechanisms. The analysis of G7 trade dynamics for 2015–2023 reveals two dominant models—export-oriented (Germany, Italy, Canada) and import-dependent (USA, France, Japan, United Kingdom)—shaped by industrial structure and foreign policy. Ukraine, in contrast, demonstrates vulnerability to external shocks, with the deepest trade deficit recorded in 2022–2023 due to war, port blockades, and declining industrial exports. Agricultural goods remain dominant, while industrial output and logistics infrastructure suffer significant losses. On this basis, the article proposes a hierarchical model integrating strategic, institutional, and operational components of export development. Its implementation would strengthen export-oriented industries, modernize infrastructure, improve human capital, and enhance Ukraine’s resilience in global trade. The proposed framework can thus serve as a foundation for post-war economic recovery and the formation of an effective state export support policy adapted to contemporary geopolitical and economic challenges.
Keywords: export potential of Ukraine; foreign trade; trade experience of G7 countries; trade balance; economic security; foreign economic activity; export strategy; import; export infrastructure; human capital